COVID-19 era: effective social distancing is a new normal for the world. (17th September 2021) - Dutta, Brij Mohan; Srivastava, Sachin Kumar
Human beings are familiar with diseases and epidemics since starting of the mankind. The mankind also knows how to fight with diseases and epidemics. After every epidemic, mankind sets new rules and laws for their survival. COVID-19 is also affecting humans badly and mankind will also set some new rules. Every human being wants to live safely and survival is the most important thing for humans' life. Safety is not only prime concern for humans but also it is the most important issue for the country too. Safe and secure life is the necessity to attain happiness. In COVID-19 epidemic social distancing is one of the major precautions to save mankind. In this work researchers have informed upon the importance of social distancing to save ourselves from COVID-19.